CHARACTERISTICS OF FORMING TOLERANT BEHAVIOR IN PUPILS OF GENERAL EDUCATION SCHOOL - Abseit Trijanovich Rustemov (Galaxy International Interdisciplinary Research Journal, 2023)
The article deals with the formation of the concept of tolerance among students of a comprehensive school in adolescence.